CHARLES MARIE WIDOR’S GOTHIQUE AND ROMANE SYMPHONIES – THE SPIRITUAL STATEMENTS OF A GRAND COMPOSER - BOGNÁR MIKLÓS, Noémi (Studia Universitatis Babes-Bolyai Musica, 2009)
In the following work I tried to present the last two symphonies composed by one of the greatest representatives of the French symphonic style: Charles Marie Widor.